Penilaian Kinerja Berbasis Siswa melalui Balanced Scorecard: Studi Mixed-Method terhadap Kepuasan, Retensi, dan Pengalaman Belajar di Pendidikan Menengah - Setiawan, Fiki; Iyus Yuswara; Marta Neka; Ayu Widiyana; Ade Tutty R. Rossa (Jurnal Kajian dan Penelitian Umum, 2026)
The evaluation of educational quality has shifted from a narrow focus on academic achievement toward more holistic, multidimensional frameworks that capture student experience and well-being. Although the Balanced Scorecard (BSC) is increasingly adopted in education, its customer perspective is frequently reduced to superficial satisfaction measures, while its application in secondary education, particularly in developing countries, remains underexplored and dominated by single-method quantitative designs. This study operationalizes and empirically validates a student-centered customer perspective of the BSC in secondary education, focusing on academic services, non-academic services, learning experience, student satisfaction, and retention. Employing an explanatory sequential mixed-methods design, quantitative survey data were collected from students at a public junior high school in Indonesia using stratified random sampling, followed by semi-structured interviews analyzed thematically. The findings reveal that overall student-centered performance is high, with academic services, especially teaching clarity and quality, rated as the strongest dimension, whereas non-academic services such as extracurricular activities and facilities received comparatively lower scores. Crucially, learning experience emerged as the primary interpretive lens through which students evaluate institutional performance, while satisfaction proved to be an affective, experience-based outcome rather than a purely cognitive judgment, and high retention reflected emotional attachment and a sense of belonging. These results suggest that student-centered performance is simultaneously measurable and experiential, and that BSC implementation in education should shift from an outcome-oriented orientation toward a meaningful, experience-driven approach to evaluating educational quality.